FRI0305 Phase 2 trial of induction therapy with anti-cd20 (RITUXIMAB) followed by maintenance therapy with anti-baff (BELIMUMAB) in patients with active lupus nephritis. (12th June 2018) - Aranow, C.; Dall'Era, M.; Byron, M.; Ding, L.; Smilek, D.; Diamond, B.; Wofsy, D.; ,
Abstract : Background: Despite case series suggesting efficacy, controlled trials of anti-CD20 in lupus nephritis (LN) did not confirm benefit; Arthritis Rheum 2012 64:1215 and 2013;65:2368). Objectives: One possible explanation for this failure stems from the fact that B cell depletion stimulates production of B cell activating factor (BAFF) which, in turn, facilitates maturation of autoreactive B cells in lymphoid organs or during B cell repopulation. The CALIBRATE study (NCT 02260934) was designed to test this hypothesis, to determine whether addition of anti-BAFF could enhance the clinical effects of anti-CD20, and to assess safety of the combination. Methods: Forty-three patients with active LN despite conventional treatment enrolled in a prospective randomised open-label trial that compared two treatment strategies. All subjects received iv rituximab (1000 mg), CTX (750 mg), and methylprednisolone (100 mg) at wks 0 and 2, followed by 40 mg/d prednisone tapered to 10 mg/d by wk 12. At wk 4, subjects received either belimumab (10 mg/kg iv at wks 4, 6, 8 and then every 4 wks) plus prednisone (n=21) or prednisone alone (n=22). Complete response (CR) was defined as: (i) urine protein:creatinine ratio (UPCR) <0.5; (ii) eGFR ≥120 or, if <120, eGFR >80% of screening; and (iii) prednisone tapered to 10 mg/d. The definiton of partial response (PR) differed only in the UPCR criterion (>50% reduction). Results: The clinical outcome at wk 24 was similar in both groups (table 1). The CR rate was 24% in the belimumab group (RCB) and 23% in the control group (RC). Three subjects in each group withdrew (WD) prior to wk 24 (two withdrawals in each group due either to progressive nephritis or an infusion reaction, and one in each group for reasons unrelated to SLE or its treatment). B cell depletion from blood was virtually absolute in both groups at wk 12, but the pace of recovery differed. Six subjects experienced serious adverse events between wks 0 and 24; three subjects in the RC group (pneumonia followed by LN flare; deep vein thrombosis; SLE flare); and three subjects in the RCB group (anti-CD20 infusion reaction; soft-tissue abscesses prior to anti-BAFF treatment; quadriceps tendon rupture). Median B Cell Count Median IgG Level CR PR NR WD Wk 0 Wk 12 Wk 24 Wk 0 Wk 24 RC Group 23%–23% 41%–14% 105 1 31 1050 1100 RCB Group 24% 24% 38% 14% 143 1 3 984 837: Conclusions: An interim analysis of data from CALIBRATE shows: (i) anti-BAFF following anti-CD20 for LN did not improve clinical outcome at week 24; (ii) anti-BAFF delayed blood B cell reconstitution following B cell depletion; and (iii) anti-BAFF following anti-CD20 was not associated with hypogammaglobulinemia or an increase in serious infections. Further analyses at 48 weeks and beyond will address how anti-BAFF therapy affects quantitative and qualitative recovery of B cells as well as long-term clinical outcome. Acknowledgements: Conducted by ITN with support from NIAID (UM1AI109565) and Genentech. Disclosure of Interest: C. Aranow Grant/research support from: GlaxoSmithKline, Consultant for: GlaxoSmithKline, M. Dall'Era Consultant for: Genentech, M. Byron: None declared, L. Ding: None declared, D. Smilek: None declared, B. Diamond: None declared, D. Wofsy Consultant for: GlaxoSmithKline, Celgene, Novartis, UCB, Sanofi